A Value-Based Approach to Qur’an Exegesis: A Study of Qur’anic Address (nidāᵓ) in Surahs Luqman and Al-Ḥujurāt - Ridoine Lahdeb (مجلة كلية الشريعة والدراسات الإسلامية, 2025)
Objectives: This study seeks to draw scholarly attention to an important exegetical approach —value-based — which, despite being implicitly recognized by several exegetes, has not been systematically explored as an independent field. It applies the value-based approach to the Qur’anic address (al-nidāᵓ al-qurᵓānī) to humanity in two specific verses from the chapters of Luqman and Al-Ḥujurāt (The Private Apartments).